Scaffolding instruction for improvement in learning English language skills - Bani Arora; Hasan Al-Wadi; Ernest Afari (Institute of Advanced Engineering and Science, 2024)
Students who learn English as a foreign language (EFL) or English as a second language (ESL) often struggle with limited vocabulary and poor reading comprehension skills. This action research explores the effectiveness of implementing scaffolding instruction for university level EFL/ESL students in improving their language learning skills, namely critical reading, and study skills for reading. A sample of 36 foundation year students was involved in two cycles of intervention. Triangulation of data collection was done after each cycle through student survey (SS), language learning assessment (LLA) tasks and an observation checklist to measure the impact of the proposed practice on the improvement in the participants’ learning. The scaffolding techniques used were soft versus hard (support provided only till needed), chunking (breaking down information), modelling (giving clear examples), bridging (using prior knowledge) and contextualizing (making connections). Both the quantitative and qualitative data revealed that scaffolding instruction significantly improved the participants’ language learning skills. For sustainable education, the findings emphasize the importance of conducting scaffolding instruction in small groups, assigning pre-planned and well-structured tasks with clear instructions, and providing scaffolding ‘as and when needed’ especially in a mixed ability group of EFL/ESL students.